Revisiting Geologic Storage Potential in Unconventional Formations Is Key to Proactive Decision Making on CCS in India - Singh, Udayan; Sharma, Naushita; Dunn, Jennifer B. (Frontiers in Climate, 2021)
Global energy modeling exercises project significant deployment of CO2 capture and storage (CCS) to bridge the gap between India’s pledged climate commitments and the 1.5 deg. C target. Despite advances in laboratory analyses and process modeling, the information on geologic storage potential in India is limited. Prior studies indicate that the vast majority of storage potential exists in saline aquifers (50-300 Gt-CO2); though, this might be overestimated. These estimates also estimate the theoretical potential in coal seams to be <5 Gt-CO2 while shale basins have not been evaluated as geologic CO2 sinks on a systems level. Based on several recent climate developments and CCS best practices, we suggest revisiting these potential estimates. We demonstrate how revisiting some assumptions might enhance the coal repository available as a sink by a factor of 7-8. We also present proof-of-concept analysis to show that Indian shale reservoirs might have suitable CO2 adsorption capacity. With detailed recommendations for revising these estimates, we present a methodological framework for incorporating the best practices for coal seam and shale basin storage potential. Based on source-sink mapping exercises, we also argue that unconventional basins in India are especially relevant because of their proximity to large point sources of CO2.